High temperature oxidation behaviour of AISI 321 stainless steel with an ultrafine-grained surface at 800 °C in Ar–20 vol.% O2. (February 2020) - Pour-Ali, Sadegh; Weiser, Martin; Truong Nguyen, Nhat; Kiani-Rashid, Ali-Reza; Babakhani, Abolfazl; Virtanen, Sannakaisa
Highlights: Early oxidation behaviour of a surface nanocrystallized 321 AISI is investigated. SNC postpones the onset of breakaway oxidation of 321ASS. Scale on the surface nanocrystallized 321ASS is dense and protective for 150 h oxidation. The thickness and uniformity of Cr-rich oxide layers are significantly affected by SNC. Schematic models are developed to describe the oxidation mechanisms. Abstract: Oxidation behaviour of surface nanocrystallized 321 austenitic stainless steel (SN–321ASS) and its conventional polycrystalline counterpart (CP–321ASS) in Ar + 20% O2 at 800 °C is comparatively investigated. Severe breakaway oxidation sets in for the CP–321ASS after 100 h, while the SN–321ASS shows a higher oxidation resistance. Surface nanocrystallization increases the diffusion and flux of Cr towards the oxidation front, and can consequently promote the kinetics of early oxidation and accelerate the formation of a thicker Cr-rich inner oxide layer, which aids in prohibiting the enhanced formation of Fe-rich oxides.